Neuropsychological differences between obsessive-compulsive washers and checkers: a systematic review and meta-analysis - Leopold, Rebecca; Backenstraß, Matthias (Journal of anxiety disorders, 2015)
Inconsistent results in neuropsychological research of obsessive-compulsive disorder (OCD) may be the result of the heterogeneous nature of OCD symptoms. The most frequently investigated symptoms are contamination/cleaning and doubt/checking. The aim of this review was to determine whether OCD washers and checkers differ in their neuropsychological performance. We conducted a meta-analysis of 13 studies (including 535 patients) comprising tests in 10 different neuropsychological domains. Washers showed significant better task performance than checkers in 8 of 10 cognitive domains. Large effect sizes were found in planning/problem solving and response inhibition. Effect size in set shifting was medium, whereas effect sizes in attention, processing speed, encoding, verbal memory and nonverbal memory were small. Limitations consisted in a relatively small number of primary studies. In line with current neurobiological findings, the results provide further evidence for the validity of different symptom dimensions in OCD. Clinical and theoretical implications are discussed.
Gesehen am 17.06.2020